ChAdOx1 nCoV-19 protection against SARS-CoV-2 in rhesus macaque and ferret challenge models - Teresa Lambe (Nature Portfolio, 2021)
Lambe, Spencer, Thomas, Gilbert and colleagues report on the detailed immune profile of rhesus macaques and ferrets vaccinated against SARS-CoV-2 under high dose challenge. Their findings indicate that the ChAdOx1 nCoV-19 (AZD1222) the vaccine induces immune responses and reduces disease symptoms in both models, including SARS-CoV-2 mediated pneumonia and virus shedding.